1984
DOI: 10.1161/01.str.15.6.1061
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence in hypoxic brain--the first report. Correlation between energy metabolism and free radical reaction.

Abstract: SUMMARY The possibility that cerebral ischemia or cerebral hypoxia may initiate a series of free radical reactions in brain tissue lipid constituents was explored by measuring sequential changes in chemiluminescence values and energy metabolism during brain hypoxia in the rat. Brain hypoxia was induced by means of arterial hypoxemia (PaO 2 17-22 mmHg), normocapnia (PaCO 2 28-38 mmHg) and normotension (MABP 100-140 mmHg). To obtain lowered PaO 2 , 4% O 2 -96% N 2 mixed gas was used. Analysis of the chemilumines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1
3

Year Published

1986
1986
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 27 publications
4
49
1
3
Order By: Relevance
“…Then, resuscitation with resultant reperfusion and reoxygenation would activate the prostaglandin endoperoxide synthase pathway further with production of prostanoids (24) and generation of oxygen free radicals. Our study doesn't rule out that substantial superoxide anion also could be produced during the asphyxia period, as has been suggested by Imaizumi et al (25). However, based upon an earlier study (24), we believe that most of the superoxide anion is produced during reventilation.…”
Section: Selzures Ischirep Asph/rev Bloodcontrasting
confidence: 50%
“…Then, resuscitation with resultant reperfusion and reoxygenation would activate the prostaglandin endoperoxide synthase pathway further with production of prostanoids (24) and generation of oxygen free radicals. Our study doesn't rule out that substantial superoxide anion also could be produced during the asphyxia period, as has been suggested by Imaizumi et al (25). However, based upon an earlier study (24), we believe that most of the superoxide anion is produced during reventilation.…”
Section: Selzures Ischirep Asph/rev Bloodcontrasting
confidence: 50%
“…14 Germane to this study is the observation that chemiluminescence occurs in brain homogenates obtained from hypoxic rats, a phenomenon considered to result from hypoxia-induced lipeperoxidation. 3 The methodology in the current study is that used by Boveris et al 6 They showed that free radical-induced lipoperoxidation resulting from infusion of ethyl and tbutyl hydroperoxides into the portal vein was accompanied by hepatic light emission. As much as a 30-fold increase in light output was observed; chemiluminescence decreased within 10-15 rain after discontinuing the infusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been many reports which support the postulation that allopurinol may act effectively on ischemia and reperfusion-induced cerebral injury in spontaneously hypertensive rats by inhibiting the free radical formation. Imaizumi et al 16 have suggested the formation of free radical in hypoxic brain as well as post-hypoxic brain. Vitamin E, a radical scavenger, has been reported to suppress the reperfusion-induced cerebral injury in spontaneously hypertensive rats of the same strain as those we used in the present study, suggesting the involvement of free radical in the genesis of cerebral injury.…”
Section: Discussionmentioning
confidence: 99%